Use of Cannabis to Relieve Pain and Promote Sleep by Customers at an Adult Use Dispensary. Issue 5 (20th October 2019) - Bachhuber, Marcus; Arnsten, Julia H.; Wurm, Gwen
ABSTRACT: Medical cannabis patients consistently report using cannabis as a substitute for prescription medications; however, little is known about individuals accessing cannabis through adult-use markets. A survey at two retail stores was conducted in Colorado, United States. Between August 2016 and October 2016, store staff asked customers if they wanted to participate and, if so, provided an electronic survey link. All customers reporting medical certification were excluded. Of 1, 000 adult-use only customer respondents, 65% reported taking cannabis to relieve pain and 74% reported taking cannabis to promote sleep. Among respondents taking cannabis for pain, 80% reported that it was very or extremely helpful, and most of those taking over-the-counter pain medications (82%) or opioid analgesics (88%) reported reducing or stopping use of those medications. Among respondents taking cannabis for sleep, 84% found it very or extremely helpful, and most of those taking over-the-counter (87%) or prescription sleep aids (83%) reported reducing or stopping use of those medications. De facto medical use of cannabis for symptom relief was common among adult-use dispensary customers and the majority reported that cannabis decreased their medication use. Adult use cannabis laws may broaden access to cannabis for the purpose of symptom relief.